FORMAL ANALYSIS OF “SEMA-I MEVLÂNÂ” - Mümtaz Sarıçiçek (Zeitschrift für die Welt der Türken, 2014)
A literary text consists of form and content. The aim of text analysis is search of aesthetic value. In this study, “Sema-ı Mevlana" poem, by Asaf Halet Celebi's is analized with formal aspects. This poem is arranged in the form of "free” verse. However, this freedom isn’t "formlessness" but is originality. Poet, has benefited from the tradition of the "folk poetry" its chapter and verse formation. In contrast, the relationship between form and content is contrary to tradition. Because determining form the content in the tradition, content has determined the format in this poem. Asaf Halet, Mevlevi poet, has established parallels between formal elements with "sema ceremony”.